2005
DOI: 10.1111/j.1523-1755.2005.67131.x
|View full text |Cite
|
Sign up to set email alerts
|

Low hematocrit predicts contrast-induced nephropathy after percutaneous coronary interventions

Abstract: Lower hematocrit is an important risk factor for contrast-induced nephropathy. Whether correcting the hematocrit prepercutaneous coronary intervention might decrease the rates of contrast-induced nephropathy should be addressed in a prospectively designed trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
2
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 23 publications
(22 reference statements)
13
137
2
10
Order By: Relevance
“…24 Nikolsky, et al found the incidence of CIN after percutaneous coronary intervention was 13.9%. 23 Shaheen found the incidence of CIN after coronary angiography and percutaneous coronary intervention was 10%. 9 McCullough, et al also stated that incidence of CIN can rise to 50% or more in patients with multiple risk markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Nikolsky, et al found the incidence of CIN after percutaneous coronary intervention was 13.9%. 23 Shaheen found the incidence of CIN after coronary angiography and percutaneous coronary intervention was 10%. 9 McCullough, et al also stated that incidence of CIN can rise to 50% or more in patients with multiple risk markers.…”
Section: Discussionmentioning
confidence: 99%
“…12 But Nikolsky, et al found about half of the patients had unstable angina. 23 The volume of contrast administered (£ 150ml), in normal blood glucose group was 30% and high blood glucose group was 36% but >150ml of contrast was administered 70% in normal blood glucose group and 64% in high blood glucose group. The difference in receiving contrast volume between two groups was not statistically significant (P>0.05).The results are consistent with Shaheen.…”
Section: Discussionmentioning
confidence: 99%
“…In a large registry of 6,773 consecutive patients treated with PCI, low baseline hematocrit was identified as an independent predictor of CIN by multivariate analysis [27]. CIN (increase of 25% or 0.5 mg/ dL over preprocedure serum creatinine, at 48 hr postprocedure) rates steadily increased with baseline hematocrit quintile decrements (from 10.3% in the highest quintile to 23.3% in the lowest quintile) (P for trend < 0.0001).…”
Section: Anemiamentioning
confidence: 99%
“…Given the high prevalence of diabetes in the general population and its ability to cause broad spectrum of cardiovascular diseases, which require radiological procedures for their diagnosis and treatment, diabetic patients represent a significant proportion of those undergoing contrast exposure. Risk of CIN is increased even in diabetics with preserved renal function [24,27]. Presence of other risk factors, such as renal insufficiency or proteinuria, in diabetics further increases the risk for CIN.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Many studies have demonstrated that pre-existing abnormal renal function is a risk factor for drug-induced nephrotoxicity 23 . As a result, in those patients with mildly decreased renal function, anticancer drugs, antineoplastic or supportive care, should be cautiously selected in order to administer drugs that are not or are less nephrotoxic.…”
Section: Linking Powered By Extylesmentioning
confidence: 99%